PSYCHIC DISTANCE, FIRM SIZE, PERCEIVED RISK AND EXPORT MARKET CHOICE OF EXPORTING FIRMS IN UGANDA - Nuwagaba, Dennis; Ntayi, Joseph M.; Ngoma, Mohammed (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿The purpose of study was to investigate the relationship between psychic distance, firm size, perceived risk and market choice of Uganda’s exporting firms. The research question is based on the fact that there is a notable shift of Uganda’s firms from exporting to markets that are geographically distant to nearer regional markets, a situation that could be attributed to psychic distance which leads to higher levels of perceived risk that the small and medium sized Ugandan firms could be trying to avoid due to their limited resources. The study used a cross-sectional research design and collected quantitative data using a structured questionnaire from a sample of 80 exporting firms of which only 72 questionnaires were used for analysis. The analysis indicated that psychic distance is positively correlated with the perceived risk while it was also established that psychic distance was negatively correlated to export market choice. The regression showed that both psychic distance and perceived risk were found to be having a significant effect on export market choice. The study recommends that firms should invest in psychic reducing activities and these could include; participating in international trade exhibition in countries perceived to be psychically distant and recruit psychically sensitive employees and/or export managers who are internationally exposed, multilingual and can understand other languages and cultures in the foreign market. Governments can also seek out trade arrangements with distant countries to facilitate trade amongst themselves in a a harmonized trade environment that is free of differences.